The HEARRT-C Score: Is Aspirin Protective in COVID-19 Patients? A Single-Centre Retrospective Study - Zeynep Kumral; Ali Canturk; Ahmet Anil Baskurt; Abdullah Taylan; Ayse Colak; Ozer Badak (COVID)
This study aimed to develop a scoring system to predict mortality risk in hospitalised COVID-19 patients using clinical, laboratory, and imaging data. A retrospective analysis was conducted at a single centre, including 325 patients admitted between March 2020 and December 2021. The data collected included patient demographics, laboratory results, medications, and thoracic CT images. Pulmonary involvement was assessed using the CO-RADS classification, while coronary artery calcification (CAC), aortic calcification, and epicardial adipose tissue were evaluated with specific scoring methods. Mortality predictors were identified through univariate and multivariate Cox proportional hazards models. The key mortality predictors identified in this study were an age above 67 years, elevated high-sensitivity troponin levels, a heart rate greater than 100 bpm, an oxygen saturation below 90%, the presence of CAC and aortic calcification, low haemoglobin levels, and the absence of acetylsalicylic acid (ASA) use at admission. The developed HEARRT-C scoring system demonstrated a strong predictive ability, with an area under the curve (AUC) of 0.91, showing 81% sensitivity and 86% specificity for predicting mortality. This study concluded that the HEARRT-C score is an effective tool for early risk stratification in COVID-19 patients, which may guide management decisions and emphasise the importance of cardiovascular factors and the potential protective role of ASA.